Pengaruh Fraud Risk Factor Menurut Fraud Pentagon terhadap Kecurangan Laporan Keuangan - Maria Sofa; Mu'minatus Sholichah (Prodi Akuntansi - FEB Universitas Muhammadiyah Gresik, 2019)
This study aims to test the effect of pentagon fraud on financial statement fraud on property and real estate companies. This study selected property and real estate sub-sector companies listed on the Indonesia Stock Exchange in 2016-2018 as the study population. The sample selection method is done by using a purposive sampling method and obtains 34 companies as research samples with 102 observations. Testing in this study uses logistic regression that was tested with the help of SPSS 15. The results obtained from this study explain that financial targets, auditor quality, and the frequent number of CEO picture's effect on financial statement fraud, while financial stability, external pressure, managerial ownership, nature of the industry, ineffective monitoring, auditor change, auditor opinion, change in director, and political connection of CEO do not affect financial statement fraud.